2007
DOI: 10.1590/s0100-40422007000200023
|View full text |Cite
|
Sign up to set email alerts
|

Otimização do banho eletrolítico da liga Fe-W-B resistente à corrosão

Abstract: Recebido em 2/2/06; aceito em 12/6/06; publicado na web em 28/11/06 OPTIMIZATION OF THE ELECTROLYTIC BATH FOR ELECTRODEPOSITION OF CORROSION RESISTANT Fe-W-B ALLOYS. A study on optimization of bath parameters for electrodeposition of Fe-W-B alloys from plating baths containing ammonia and citrate is reported. A 2 3 full factorial design was successfully employed for experimental design analysis of the results. The corrosion resistance and amorphous character were evaluated. The bath conditions obtained for dep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
7

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 20 publications
0
3
0
7
Order By: Relevance
“…The coating alloys were obtained by induced deposition of Ni, Co, and W in a plane copper foil of 0.0008 m 2 surface area. The substrate was previously treated by polishing with 200 and 400 grade abrasive paper, followed by chemical treatment with 10 g/g sodium hydroxide solution and 1 L/L sulphuric acid …”
Section: Methodsmentioning
confidence: 99%
“…The coating alloys were obtained by induced deposition of Ni, Co, and W in a plane copper foil of 0.0008 m 2 surface area. The substrate was previously treated by polishing with 200 and 400 grade abrasive paper, followed by chemical treatment with 10 g/g sodium hydroxide solution and 1 L/L sulphuric acid …”
Section: Methodsmentioning
confidence: 99%
“…In this case, they observed that reducing the concentration of NiCl 2 •6H 2 O, the concentration of NaBH 4 , and the temperature significantly influenced the deposition of the nickel coating. Santana et al [30] studied the optimization of the electrolytic bath for electro-deposition of corrosion-resistant Fe-W-B alloys using multi-response optimization. In their case, a full factorial design was considered for the design of the experiments.…”
Section: Electroplating Process Factors Examined By Use Of Rsmmentioning
confidence: 99%
“…Os experimentos foram realizados em duplicata e em ordem aleatória para evitar erros sistemáticos. Para análise estatística dos resultados foi utilizado o pacote estatístico do software STATISTICA© versão 8.0 [8,16,22]. A Tabela 2 apresenta os valores reais e codificados dos parâmetros operacionais avaliados neste trabalho.…”
Section: Materiais E Métodosunclassified